Reciprocal Expertise Affirmation and Shared Expertise Perceptions in Work Teams: Their Implications for Coordinated Action and Team Performance. Issue 3 (16th February 2012) - Grutterink, Hanneke; Van der Vegt, Gerben S.; Molleman, Eric; Jehn, Karen A.
Abstract : In this paper we argue that reciprocal expertise affirmation—i.e. the mutual recognition by team members that they respect, value, and affirm each other's expertise—is positively related to team performance, but only in teams with high levels of shared expertise perceptions. Moreover, we propose that the joint effects of teams' reciprocal expertise affirmation and sharedness of expertise perceptions on team performance will be mediated by coordinated action. Data from 226 members of 39 student teams, working on a realistic four‐week business simulation, supported our hypotheses. Our findings highlight the importance of reciprocal expertise affirmation for the effective functioning of work teams.